You are here : a portable history of the universe - Potter, Christopher, 1959- (New York : Harper Perennial, 2009)
A dazzling exploration of the universe and our relationship to it, as seen through the lens of today's most cutting-edge scientific thinking.
Orientation -- 26 degrees of separation -- Measure for measure -- It's not about you -- Going through the motions -- The other way out -- Light on the matter -- Something and nothing -- Hail the birth of stars -- Homing in -- Beginning the begats -- In and out of Africa -- We are there.
Includes bibliographical references : (pages [275]-279) and index.
Keywords: Cosmology -- Popular works; Science -- History; Science -- Philosophy